Body girdle reduced fat deposition and altered other body parameters in rats - Li, T-R.; Chen, B-C.; Zou, Y-F.; Zhang, J.; Zhang, W.; Dong, B.; Li, X.; Chen, X-F. (Cellular and Molecular Biology, 2015)
Many women favor in wearing foundation garments to shape their body and show satisfactory figures. However, few investigations have been conducted on the physiological impact of wearing tight garments on the body. In this study, we used girdled rats that were fed with a high fat diet to investigate their physiological condition including alterations in food intake, body weight, fat deposition, and hormone concentrations. Over the experiment period, girdled rats maintained normal plasma and liver cholesterol and triglyceride. Leptin level in girdled rats was significantly lower than that in normal control. The fat tissue of girdled rats was more active in secretion of leptin, which might be mediated by mTOR signaling. Girdled rats showed no difference in hematology analysis during the experiment period. This study showed that a body girdle can significantly reduce fat deposition and alter other body parameters in rats.